Multi-parametric flutter analysis of a morphing wing trailing edge. (September 2014) - Pecora, R.; Magnifico, M.; Amoroso, F.; Monaco, E.
Abstract: The development of adaptive morphing wings has been individuated as one of the crucial topics in the greening of the next generation air transport. Research programs are currently running worldwide to exploit the potentiality of morphing concepts in the optimisation of aircraft efficiency and in the consequent reduction of fuel burn. Among these, SARISTU represents the largest European funded research project which ambitiously addresses the challenges posed by the physical integration of smart concepts in real aircraft structures; for the first time ever, SARISTU will experimentally demonstrate the structural feasibility of individual morphing concepts concerning the leading edge, the trailing edge and the winglet on a full-size outer wing belonging to a CS-25 category aircraft. In such framework, the authors intensively worked on the definition of aeroelastically stable configurations for a morphing wing trailing edge driven by conventional electromechanical actuators. Trade off aeroelastic analyses were performed in compliance with CS-25 airworthiness requirements (paragraph 25.629, parts (a) and (b)-(1)) in order to define safety ranges for trailing-edge inertial and stiffness distributions as well as for its control harmonics. Rational approaches were implemented in order to simulate the effects induced by variations of trailing-edge actuators' stiffness on the aeroelastic behaviour of the wing also in correspondence of different dynamic properties of the trailing-edge component. Reliable aeroelastic models and advanced computational strategies were properly implemented to enable fast flutter analyses covering several configuration cases in terms of structural system parameters. Already available finite elements models were processed in MSC-NASTRAN ® environment to evaluate stiffness and inertial distributions suitable for the stick-equivalent idealisation of the reference structure. A parametric stick-equivalent model of the reference structure was then generated in SANDY3.0, an in-house developed code, that was used for the definition of the coupled aero-structural model as well as for the solution of aeroelastic stability equations by means of theoretical modes association in frequency domain. Obtained results were finally arranged in stability carpet plots efficiently conceived to provide guidelines for the preliminary design of the morphing trailing-edge structure and therein embedded actuators.